(untitled) (Materiali di Estetica. Terza serie, 2017)
Image, Language, Picture by Emilio Garroni has been published in 2005. The author reflects on the relationship between perception and language, mainly related to the inner image, which is defined as "the premise and the guarantee of the reality of the meaning of the words of language". This work focuses on Garroni’s relationship between perception and language showing how it provides a cause for reflection on the influence that technical devices have on perception and therefore on the role of technology in structuring the sensitivity. Does the interactivity introduced by the new media authorise us to talk about the anesthetic process and the reduction of the aisthesis? What are the suggestions can we welcome to answer this question by investigating the status of arts that compares with the digital universe and technology?